Table of Content - - (Journal of Arabic Language Sciences and Literature, 2023)
Table of Content:1. Review of Identity in The Gypsy by Weam AlmadadyProf. Adnan Mahmoud Suleiman Obaidat2. Image of The Jew in “Sleep of the Gazelles”Mr. Farid Khalil Nassar3. Renovation Regarding The Origin Of Subject Indication Concerning Al-Ragib Al-AsfahaniMrs. Wafaa Mohamed Elshahed4. The effect of semantic contrast on text interpretations in the exegesis of Al-ZamakhsharīDr. Alhassan Abdur-Rahim Husein5. Metasardic themes in the novels of Amir Taj Al-SirMr. Hossain Torfi Alivi, Co-Prof. Ali Khezri, Prof. Rasoul Balavi, Co-Prof. Mohammad Javad Pur Abed6. The Semiotics of Emotions in Diwan (wtar unajy kawsah) By Maher's Mahl AlrehailyProf. Alreem Mufwaz Alfawaz, Mrs. Mrwa Mokhtar Elgheity7. The significance of the command verb and the compatibility of the Quranic commaMr. Saad Faiz Khamis Almahaijri
Keywords: Journal of Arabic Language and Literature